1986
DOI: 10.1007/bf01907423
|View full text |Cite
|
Sign up to set email alerts
|

Renal hypertensive hypertrophy in the rat: a substrate for arrhythmogenicity

Abstract: We investigated the ability of ouabain to produce lethal arrhythmias in rats with myocardial hypertrophy resulting from chronic renal hypertension. A gradual pressure overload was produced in female Wistar rats by left renal artery stenosis (two kidney, one clip, Goldblatt hypertension). Hypertension (systolic blood pressure greater than 150 mm Hg) developed within three weeks after clipping of the left renal artery and blood pressure continued to increase for the next five weeks. At ten weeks after the onset … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
2
4
0
Order By: Relevance
“…In vivo, as mentioned above, Gul et al (2009) demonstrated a pronounced increase in cardiac ADPR cyclase activity and cADPR levels in a rat 2K1C model that is characterised by increased angiotensin-II levels, hypertension and cardiac hypertrophy. Interestingly, 2K1C rats display an increased propensity towards ouabain-induced ventricular arrhythmia (Capasso et al 1986) which was shown to be improved in our study here by administration of inhibitors of cardiac ADPR cyclase.…”
Section: Discussionsupporting
confidence: 64%
“…In vivo, as mentioned above, Gul et al (2009) demonstrated a pronounced increase in cardiac ADPR cyclase activity and cADPR levels in a rat 2K1C model that is characterised by increased angiotensin-II levels, hypertension and cardiac hypertrophy. Interestingly, 2K1C rats display an increased propensity towards ouabain-induced ventricular arrhythmia (Capasso et al 1986) which was shown to be improved in our study here by administration of inhibitors of cardiac ADPR cyclase.…”
Section: Discussionsupporting
confidence: 64%
“…The results of the present study are in general agreement with the data of Capasso and coworkers (2). In both works it has been shown that arrhythmogenicity of ouabain is increased in the presence of myocardial hypertrophy.…”
Section: Discussionsupporting
confidence: 95%
“…It has already been proved that the arrhythmogenicity of digitalis is increased in rats with left ventricular hypertrophy due to experimental renal hypertension (2). However, in explanation of this finding, the possible electrolyte imbalance secondary to reduced renal excretory function, has to be considered as one of the possible causes of the lower electrical stability of the myocardial cell membrane, i.e., of the increased arrhythmogenicity of ouabain.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations